Increasing energy production of a ducted wind turbine system. Issue 6 (December 2020) - Nardecchia, Fabio; Groppi, Daniele; Lilliu, Ilenia; Astiaso Garcia, Davide; De Santoli, Livio
This article focuses on evaluating the performance of a relatively new system of a ducted wind turbine with an omnidirectional capture system, the INVELOX system. In the present study, the improvement of such patented system has been developed by performing a detailed numerical analysis varying several geometrical parameters and analysing the effect of changing wind velocity and wind direction. At first, the model validation was performed and the performance of the original system against the wind direction changes was analysed observing that the highest speed ratios are obtained for two specific directions. Based on the previous results, the most critical features of the system have been identified, and then it has been approached a geometric improvement of the system aiming at increasing the system productivity. The results show there is a possibility to largely improve the overall design and extract more energy from the wind respect with the original design.